2015
DOI: 10.1364/oe.23.019777
|View full text |Cite
|
Sign up to set email alerts
|

Observation of discrete diffraction patterns in an optically induced lattice

Abstract: We have experimentally observed the discrete diffraction of light in a coherently prepared multi-level atomic medium. This is achieved by launching a probe beam into an optical lattice induced from the interference of two coupling beams. The diffraction pattern can be controlled through the atomic parameters such as two-photon detuning and temperature, as well as orientations of the coupling and probe beams. Clear diffraction patterns occur only near the two-photon resonance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…It has been shown that by applying a standing-wave beam, the higher order Fraunhofer diffraction can be obtained for a probe light due to the modulation of the refractive index. Recently, the discreet diffraction patterns established via optically induced atomic lattices have been also experimentally demonstrated 20 .…”
mentioning
confidence: 99%
“…It has been shown that by applying a standing-wave beam, the higher order Fraunhofer diffraction can be obtained for a probe light due to the modulation of the refractive index. Recently, the discreet diffraction patterns established via optically induced atomic lattices have been also experimentally demonstrated 20 .…”
mentioning
confidence: 99%
“…The standing-wave coupling field propagating along the z direction is responsible for establishing the optically induced lattice along the transverse direction x. By launching the weak signal field into the lattice, we can obtain discrete diffraction patterns [40], as well as the underlying spatially modulated susceptibility, under the EIT condition. Our results clearly indicate that by adding another standing-wave pump field, spatially periodic gain and loss regions with high contrast can be generated on the launched signal field.…”
mentioning
confidence: 99%
“…The optically induced lattice (along the transverse direction x) inside the atomic vapor cell is generated by interfering a pair of coupling laser fields from a same external cavity diode laser (ECDL). As a result, we can observe the spatially intensity-modulated probe field [28] at the output plane of the vapor cell, which implies the formation of the spatially distributed probe-field susceptibility in the atomic medium. The EIT-assisted Talbot effect is manifested through the repetition of the image on the output surface of the cell at the integer Talbot planes.…”
mentioning
confidence: 90%
“…With the near-parallel weak probe beam E 1 having an elliptical-Gaussian intensity profile from another ECDL1 launched into the induced lattice, the probe-field susceptibility can be spatially modulated under the EIT condition. [28,29] By carefully choosing the parameters such as frequency detunings and Rabi frequencies of the probe and coupling fields, clear diffracted probe beam pattern from the formed EIG can be observed at the output plane of the cell, which is monitored by utilizing a charge coupled device (CCD) camera (see Fig. 1) with an imaging lens.…”
mentioning
confidence: 99%